2015
DOI: 10.1002/stem.2016
|View full text |Cite
|
Sign up to set email alerts
|

IER3 Promotes Expansion of Adipose Progenitor Cells in Response to Changes in Distinct Microenvironmental Effectors

Abstract: Adipose tissue expansion is well-orchestrated to fulfill the energy demand. It results from adipocyte hypertrophy and hyperplasia due to adipose progenitor cell (APC) expansion and differentiation. Chronic low grade inflammation and hypoxia take place in obese adipose tissue microenvironment. Both of these events were shown to impact the APC pool by promoting increased self-renewal along with a decrease in the APC differentiation potential. However, no common target has been identified so far. Here we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…In addition, from RNA interference experiments with siRNAs to IER3 that were previously validated 7 , we observed that EGR1 expression was dependent on IER3 expression (Fig. 5G), indicating that LPV may alter IER3 prior to EGR1 .…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…In addition, from RNA interference experiments with siRNAs to IER3 that were previously validated 7 , we observed that EGR1 expression was dependent on IER3 expression (Fig. 5G), indicating that LPV may alter IER3 prior to EGR1 .…”
Section: Resultssupporting
confidence: 52%
“…We measured the ERK1/2 phosphorylation in response to activin A which is essential to maintain APs (hMADS) self-renewal 7, 8 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations